Epstein-Barr Virus, Human Herpesvirus 8, and Human T-Lymphotropic Virus Type 1 Infections Amongst Patients With Lymphoid Malignancies: Exploring Causal Relationship, in Calabar. (21st September 2018) - Bassey, Bassey; Asuquo, Marcus; Akanmu, Alani
Abstract: Objectives: To determine the prevalence of EBV/HHV-8/HTLV-1 among patients with LM and compare with controls. To determine the relationship between history of blood transfusion, socioeconomic data, and blood indices with positivity of oncogenic viruses. Methods: A total of 180 participants who gave informed consent were recruited, 60 with LM and 120 controls. Socioeconomic data and history of blood transfusion were obtained through questionnaire. Ten milliliters of blood was collected from each patient: 5 mL into EDTA for FBC and 5 mL into a plain bottle for ELISA to test for oncogenic viruses. Results: LM population had EBNA IgG prevalence of 76.7%, while controls had 75.0% ( P = .806). EBNA IgM prevalence for LM patients and controls was no different from each other (8.3%) ( P = 1.000). HHV-8 prevalence for LM patients had 5% while controls had 11.7% ( P = .149). None (0%) of the study participants was positive for HTLV-1. Participants who had never received a blood transfusion had 75.7% positivity for EBNA IgG, 9.3% for EBNA IgM, and 10% for HHV-8. Those transfused had 75% positivity for EBNA IgG, 5% for EBNA IgM, and 7.5% for HHV-8 (EBNA IgG, P = .926; EBNA IgM, P = .387; and HHV-8, P = .633). Concerning only patients with LM, 30 (65.2%) positive for EBNA IgG had received blood while 16 (34.8%) had not ( P = .666). Two (40%) positive for EBNA IgM had received blood while three (60%) had not ( P = .186). The three patients who were positive for HHV-8 had received a blood transfusion. There were statistically significant differences between the various blood indices of LM patients and the controls ( P < .05), except MCH, which was not significant ( P = .115). There was no statistically significant difference between the socioeconomic data of LM patients who were infected with the oncogenic viruses and those who were not ( P > .05). Conclusion: The study shows that oncogenic viruses are not frequently associated with LM in Calabar, and blood transfusion does not incur any additional risk.